ANALISIS PERSEPSI PETANI PETERNAK SAPI POTONG TERHADAP PERAN PENYULUH DI KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - Talibo, Repli .; Sondakh, B F.J; Sajow, A A.; Lainawa, J . (Universitas Sam Ratulangi, 2017)
ANALYSIS OF CATTLE FARMERS PERCEPTION ON THE ROLE OF EXTENSION AGENTS IN SANGKUB DISTRICT NORTH OF BOLAANG MONGONDOW REGENCY. There are about 596 cattle farmers in Sangkub county North of Bolaang Mongondow Regency. Two hundreds and ten farmers from them are being corporated in 21 farmer groups. From those twenty one farmers, seven farmer groups that are actively categorized in farming operation, while others are considered inactive anymore. The reason for that might be due to the lack of capital or farm management misconduct, or the lack of knowledge in the value of cattle farming. The present study was designed to elaborate the perception of cattle farmers on the role of extension agents in Sangkub County North ofBolaang Mongondow Regency. The research was conducted in a descriptive method that delineated phenomenon of research variables. Cattle farmers group samples were choosen purposely and finally farmers in the village of Tombolango Induk, Busisingo, and Sangkub II were included in the study. All of thirty cattle farmers were taken as samples. Variables measurement were conducted using ‘Likert Scale’ and scoring at each indicator. Research results showed that perception of cattle farmers on the role of extension agents in Sangkub County North of Bolaang Mongondow Regency can be rated as follow: in term of extension agents as facilitator: 96.67% good, 3.33% very good; extension agents as mediator: 83.33% good enough (fair), 3.33% good; extension egents as motivator: 83.33% good enough (fair), 16.67% very good; extension agents as educator: 93.33% good, 6.67% very good; extension agents as communicator: 100% good. Overall, it can be concluded that perception of cattle farmers on the role of extension agents in Sangkub County of Bolaang Mongondow Utara Regency rated 93.33% as good and 6.67% as very good. Keywords: Perception,Cattle Farmers, Extension Agents, North of Bolaang Mogondow Regency